Effect of Soil Tillage Systems and Boiler Ash Application on the Growth and Yield of Sugarcane (Saccharum officinarum L.) - Suryana, Suryana; Zuliati, Septiarini; Sukmawati, Riska; Fadillah, Resti (Jurnal Biologi Tropis, 2025)
Soil tillage and the application of organic materials such as boiler ash play a crucial role in improving soil fertility and crop productivity. This study aimed to evaluate the effects of different tillage systems and boiler ash application on the growth and yield of sugarcane (Saccharum officinarum). The experiment was arranged in a randomized complete block design (RCBD) with five treatments and three replications, involving tillage variations (plowing, harrowing, subsoiling) and 40 tons ha⁻¹ of boiler ash. Data were analyzed using the LSD test at a 5% significance level. The results showed that treatment P5 produced the best growth performance, with a plant height of 2.85 cm, stem diameter of 2.33 cm, and 15 tillers at 9 weeks after planting. This treatment also achieved the highest yield of 122.79 tons ha⁻¹, with a 7.18% increase in productivity. Positive correlations were observed between yield and plant height (R² = 0.4593) as well as stem diameter (R² = 0.793). These findings suggest that the appropriate combination of tillage techniques and boiler ash application has the potential to sustainably enhance sugarcane productivity.